(untitled) (Journal of Organizational Psychology, 2020)
The purpose of this study is to explore a faculty’s research attitudes, intentions, and behaviors (i.e., productivity) as well as the influence that a number of individual characteristics could have on research-related variables at a private business college. The results indicate that although the faculty hold favorable attitudes toward research and have strong intention to engage in future research, their actual research productivity is low. In addition, the individual characteristics of age, marital status, time spent on research, and time spent on teaching variably influence research productivity.